China Early Childhood Development : SABER Country Report 2016 - World Bank Group (World Bank, Washington, DC, 2017)
The aim of the systems approach for better education results (SABER) - early childhood development (ECD) initiative is to collect, analyze, and disseminate comparable data about national and sub-national ECD policies across countries. The data will help the World Bank assess how well overall ECD systems, and those in the education, health, and nutrition sectors in particular, meet three widely shared goals: establishing an enabling environment, implementing widely, and monitoring and assuring quality.